Analisis Penyusunan e-Book Tematik Kelas 4 Sekolah Dasar X Jakarta - Vincentia Dea Cahyaningrum; Erni Murniarti (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This article discusses the analysis of the use of grade 4 thematic e-books that have been used. This article aims to provide an overview of the successful use of e-books in elementary schools. This article was created through observation, research, and literature study, using supporting books and Education journals as well as other related documents. Use of class 4 e-books has been used since the pandemic hit the world, which made students have to study at home online. This is why the use of e-books is currently in great demand by educational institutions to support learning. The results of the study show that the use of grade 4 thematic e-books is helpful to support learning activities, especially during the pandemic, but in its preparation, there are still things that are not appropriate to be determined during the pandemic. E-books are used to make it easy for students and teachers to discuss the teaching material to be studied.